2003
DOI: 10.1152/japplphysiol.01125.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age and endurance training on the capacity for epinephrine-stimulated gluconeogenesis in rat hepatocytes

Abstract: Sumida, Ken D., Steven M. Arimoto, Michael J. Catanzaro, and Frank Frisch. Effect of age and endurance training on the capacity for epinephrine-stimulated gluconeogenesis in rat hepatocytes. J Appl Physiol 95: 712-719, 2003; 10.1152/japplphysiol.01125.2002.-The effects of endurance training on hepatic glucose production (HGP) from lactate were examined in 24-h-fasted young (4 mo) and old (24 mo) male Fischer 344 rats by using the isolated-hepatocyte technique. The liver cells were incubated for 30 min with 5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…To understand the reasons for the reduced response to β 2 -AR-stimulated intracellular function, aged rat hepatocyte viability, receptor density, receptor binding affinity, and adenylate cyclase activities were studied (Morgan et al, 1983;Fraeyman et al, 2000). The β 2 -AR number, the density, the Gs activity, and the protein levels were all unchanged in aging (Dax et al, 1987;Eakes et al, 1996;Marker et al, 1998;Sumida et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the reasons for the reduced response to β 2 -AR-stimulated intracellular function, aged rat hepatocyte viability, receptor density, receptor binding affinity, and adenylate cyclase activities were studied (Morgan et al, 1983;Fraeyman et al, 2000). The β 2 -AR number, the density, the Gs activity, and the protein levels were all unchanged in aging (Dax et al, 1987;Eakes et al, 1996;Marker et al, 1998;Sumida et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…age related decrease in the β 2 adrenergic receptor (AR), adenylate cyclase, or to Gαs expression (Dax et al, 1981Fraeyman et al, 2000. In contrast, it has been suggested that expressions of the β 2-AR, adenylate cyclase or Gαs either increase or do not change with aging (Dax, 1987;Eakes, 1996;Marker, 1998;Sumida, 2003;Jang, 2006). Thus, the questions of why and how epinephrine becomes less potent in the gluconeogenesis response in aging remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…In trained subjects, the lipolytic response of adipocytes to epinephrine was increased in comparison to fat cells from sedentary subjects (Riviere et al, ). Similarly, epinephrine stimulated gluconeogenesis was greater in hepatocytes isolated from trained compared to sedentary rats (Sumida et al, ), though it should be noted that this has not been a universal finding (Podolin et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…Exercise training influences the metabolic responsiveness to catecholamines in adipose tissue, skeletal muscle, and the liver (Plourde, Rousseau-Migneron, & Nadeau, 1993;Podolin, Gleeson, & Mazzeo, 1996;Riviere, Crampes, Beauville, & Garrigues, 1989;Sumida, Arimoto, Catanzaro, & Frisch, 2003). For example, isoproterenol-stimulated adenylyl cyclase activity was significantly elevated in soleus muscles from trained compared to sedentary rats (Plourde et al, 1993).…”
mentioning
confidence: 99%
“…This augmentation may be attributable to redistribution of vascular volume increasing glucose availability to muscle tissue. Catecholamines may also increase EGP directly or by suppressing insulin while increasing glucagon (Wasserman et al 1989;Gustavson et al 2003;Sumida et al 2003).…”
Section: Discussionmentioning
confidence: 99%